Garbage in/Garbage out: The hermeneutics of visualisation reading in humanitarian mapping and interventions - Oluoch, Isaac; Gerritsen, Isabel; Wanjiru, Nicera; Rovoga, Eric (Journal of Human-Technology Relations, 2024)
Geographic information has become increasingly relied upon in supporting decision-making in public administration as well as humanitarian intervention. One domain where such information has been important is waste management, notably improving the mapping of areas with the highest waste accumulation, finding suitable locations for landfills as well as planning transport routes for collection services. The utility of geographic information here reflects the capacity of visual information to mediate between human actors (e.g. municipal authorities) and the world in which they wish to make changes . In this paper, we shall be presenting insights from five focus groups that were conducted to assess the impact of the visualisation of waste accumulation in the ‘slums’ and informal settlements in Nairobi, Kenya, along with factors that affected the readability and understanding of the visualisations presented in the focus groups. In this paper, we will be considering: i) the impact of design elements (e.g. level of detail and symbology) on raising problem awareness of the participants regarding the waste accumulation; and ii) the ethical and political concerns that arise from the way communities living in the DUAs are perceived from the visualisations.